2003
DOI: 10.1034/j.1600-0854.2003.00133.x
|View full text |Cite
|
Sign up to set email alerts
|

Human VPS34 and p150 are Rab7 Interacting Partners

Abstract: Regulation of membrane trafficking requires the concerted actions of rab proteins, their effectors and several phosphatidylinositol 3 0 -kinases. Rab7 is required for late endosomal transport and here we establish that the phosphatidylinositol 3 0 -kinase hVPS34 and its adaptor protein p150 are rab7 interacting partners. The hVPS34/ p150 complex colocalized with rab7 on late endosomes and hVPS34 activity was dependent on nucleotide cycling of rab7. In addition, total cellular phosphatidylinositol 3 0 -phosphat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
135
1

Year Published

2005
2005
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 149 publications
(143 citation statements)
references
References 47 publications
7
135
1
Order By: Relevance
“…This finding is consistent with previous studies on the effects of PI 3-kinase inhibitors on the degradation of other signaling receptors, such as the PDGF receptor [16] and the EGF receptor [25,26] There are at least three PI 3-kinases in mammalian cells, and the most commonly used PI 3-kinase inhibitors act on all three [27]. Evidence from other studies implicates the type III PI 3-kinase hVps34 in controlling traffic to lysosomes [28,29]. Whether hVps34 is the PI 3-kinase responsible for controlling β 2 AR sorting to lysosomes will require additional studies.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…This finding is consistent with previous studies on the effects of PI 3-kinase inhibitors on the degradation of other signaling receptors, such as the PDGF receptor [16] and the EGF receptor [25,26] There are at least three PI 3-kinases in mammalian cells, and the most commonly used PI 3-kinase inhibitors act on all three [27]. Evidence from other studies implicates the type III PI 3-kinase hVps34 in controlling traffic to lysosomes [28,29]. Whether hVps34 is the PI 3-kinase responsible for controlling β 2 AR sorting to lysosomes will require additional studies.…”
Section: Discussionsupporting
confidence: 91%
“…5) is consistent with this interpretation. The molecular mechanisms underlying rab7 action are not clear at present, however a recent study shows that rab7 binds to hVps34 (a PI 3kinase) and localizes it to late endosomes [29]. PI 3-kinase inhibitors did not affect the initial rate of β 2 AR endocytosis in our system (Fig.…”
Section: Discussionmentioning
confidence: 58%
“…mechanisms or use unique molecule(s) to interact with microtubules. Two other putative Rab7 effectors, hVps34/p150 and XAPC7, might have been overlooked in our affinity screening because hVps34/p150 generally shows the highest affinity to nucleotide-free Rab7 (Stein et al, 2003), and the molecular mass of XAPC7 is 27 kDa, which was below the limit of our detection due to contamination of GST-fusion proteins.…”
Section: Significance Of the Interaction Between Ehrab7a And The Retrmentioning
confidence: 96%
“…Homology-based genome-wide search of the putative effectors of the amoebic Rab7A using known Rab7 effectors from other organisms, including RILP, Rabring7, hVps34p/p150 (phosphatidylinositol 3-kinase), and proteasome ␣-subunit (XAPC7) indicated that this organism possesses homologues for Vps34/p150 and XAPC7, but lacks RILP and Rabring7, suggestive of the presence of novel Rab7 effectors in this organism (Cantalupo et al, 2001;Mizuno et al, 2003;Stein et al, 2003;Dong et al, 2004). Thus, we attempted to isolate the effector molecules of EhRab7A by affinity purification to gain an insight in the regulation of the amoebic Rab7A.…”
Section: Identification Of a Retromerlike Complex As A Novel Ehrab7a mentioning
confidence: 99%
“…The chicken anti-Rab7 antibody (Stein et al, 2003;Dong et al, 2004) was a kind gift from Dr. Angela Wandinger-Ness, and rabbit anti-Rab7 was purchased from Santa Cruz Biotechnology (Santa Cruz, CA). Mouse monoclonal antibody (mAb) against the Xpress epitope was from Invitrogen, monoclonal lysosome-associated membrane protein-1 (Lamp-1) (H4A3) antibody was from Santa Cruz Biotechnology, and anti-p150 glued was from BD Biosciences (San Jose, CA).…”
Section: Antibodiesmentioning
confidence: 99%